Elements of solid state electronics based on soi-structures and si whiskers for cryogenic temperatures - Druzhinin, A. A.; Osrovskkii, I. P.; Khoverko, Yu. M.; Koretskyy, R. N. (Technology and design in electronic equipment, 2014)
The paper presents the study results of electrical properties of polycrystalline silicon films in silicon-on-insulator structures and Si whiskers in the temperature range of 4.2 – 70 K obtained by impedance measurements in the frequency range from 10 Hz to 250 kHz and the possibility of their use in solid-state electronics, functioning at cryogenic temperatures. Characteristics of samples obtained with impedance measurements allow predicting certain specifications of reactive elements of solid state electronics based on polycrystalline and single crystalline silicon, operable at low temperatures. Using the established dependencies, separate elements in the form of solid-state electronics capacitive and inductive elements as well as a combined system in an oscillatory circuit, operable at cryogenic temperatures, have been suggested. The features of developed system depend on the structure of samples and their doping level, which allows changing the required parameters of the elements of solid state electronics in a wide range.